Records management practices of San Sebastian College-Recoletos Canlubang a plan for the establishment of an archives and records depository - Garcia, Crizell Joy P.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
This study aims to analyze the current records management and recordkeeping system of SSC-RC and to propose the establishment of an archives and records depository for the college.
A questionnaire was distributed to the appropriate respondents from each of the 14 SSC-RC offices. The research instrument probed into the respondent's profile, the types of records that are created and maintained, the storage, filing, access, appraisal, retention and disposition practices of each office, as well as the recordkeeping problems, hindrances or issues that they are currently experiencing.
It was discovered that some of the recordkeeping practices do not conform to the ISO ideals and this is mainly because of their inadequate knowledge about the appropriate recordkeeping standards. Taking this into account, an initial floor plan, budget plan, requirements for personnel, and disposition schedule for the proposed archives and records depository are presented.
Finally, the author recommends that future studies deal with the formulation of a human resource plan and a more comprehensive disposition schedule covering all records in the inventory. More importantly, it is recommended that an acquisition and access policy be developed in the future to complete the establishment of the records and archives depository.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: San Sebastian College-Recoletos Canlubang -- Records and correspondence -- Evaluation; Records -- Management